Structural peculiarities of La2Ge1-xCrxMgO6-δ (0[removed] - López, C.A.; Singh, Preetam; Martínez-, Coronado R.; Alonso, J.A. (Elsevier Ltd, 2023)
The double perovskite La2MgGeO6 has been modified by substitution of Ge by Cr to introduce oxygen vacancies. A specimen of composition La2Ge0.55Cr0.45MgO6 has been studied by neutron diffraction, in the 300–873 K temperature range. The perovskite structure can be defined in the rhombohedral R3 space group. At 295 K, the unit-cell parameters are a = 5.5115 (2), c = 13.3485 (7) Å and V = 351.16 (3) Å3. This double perovskite exhibits two distinct crystallographic sites for Mg and (Cr,Ge), statistically distributed at the octahedral sites. It presents a conspicuous deficiency at O1 sites, accounting for the excellent ionic conduction properties. The Bond-Valence Energy Landscape (BVEL) map at 873 K shows that oxygen atoms present a higher mobility around the (Ge/Cr)O6 octahedra than the MgO6 ones; therefore, the “bottleneck” points for oxygen mobility are placed between the (Ge/Cr)O6 octahedra around the La3+ and Mg2+ cations. The dark-red samples prepared in air show evidence of oxidation of some Cr3+ to Cr4+ to give a polaronic component to a conductivity of 10−2 Scm−1 at 300 °C for La2Ge0.5Cr0.5MgO6-δ; Arrhenius plots of conductivity obtained on cooling from 900 °C to 25 °C in air give an activation energy of ∼0.25 eV. The fuel-cell performance at 600 °C gave a power density of 606 mW cm−2, a threefold increase over the output compared with LSGM electrolyte.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Defect perovskite structure; Neutron diffraction; Oxygen vacancies; Solid-oxide electrolyte; Oxygen vacancies; Activation energy; Germanium compounds; Lanthanum compounds; Magnesium compounds; Neutron diffraction; Perovskite; Solid electrolytes; Solid oxide fuel cells (SOFC); Temperature